Intentions to Steal: How Equal is the Interplay Between Anticipated Moral Emotions and Self-Serving Justifications Across Male and Female Young People? - De Buck, Ann (Victims & offenders, 2025)
The present study is concerned with the interplay between anticipated moral emotions and self-serving justifications in the explanation of intentions to steal. Theoretically, it has been suggested that both moral dimensions may interact in such a way that their effects amplify each other. This amplification hypothesis has rarely been tested. The following research question is addressed: To what extent do anticipated moral emotions amplify the impact of self-serving justifications on intentions to steal? To assess the stability of the findings, the hypothesis is tested across males and females. Online survey data are obtained from a large convenience sample of young people (N = 3584). A visual vignette was used to elicit participants’ offense-specific responses to the key concepts. Evidence suggests that self-serving justifications in the specific context of stealing and anticipated shame-guilt have strong main effects on intentions to steal. A statistically significant interaction effect is found in the full sample and the female subsample, suggesting that participants reporting weak anticipated shame and guilt are most likely to form intentions to steal in the presence of self-serving justifications. However, the effect is small and not found in the male subsample. We discuss the limitations and implications for further research.